Aesthetics of temporal and spatial transformations in virtual environments. Issue 2 (1st December 2014) - Reyes-Garcia, Everardo
Our common interaction with media based on motion, time and screen, such as cinema, television, video and animation, is built on the depiction of visual images one after another: the same visual space is rewritten continuously. Throughout history there have been alternative methods for interacting with a sequence of frames. Pioneering techniques like chronophotography and cyclography shared the same interests of recent artworks and scientific visualizations in capturing, tracing and representing movement in space. In this article, we introduce an experimental approach to represent video artworks as 3D models in virtual environments. Our aim is to contribute to the possibilities offered by contemporary computing techniques to explore alternative ways of interacting with motion media.